If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(5x + 6) = 0 Reorder the terms: (2 + x)(5x + 6) = 0 Reorder the terms: (2 + x)(6 + 5x) = 0 Multiply (2 + x) * (6 + 5x) (2(6 + 5x) + x(6 + 5x)) = 0 ((6 * 2 + 5x * 2) + x(6 + 5x)) = 0 ((12 + 10x) + x(6 + 5x)) = 0 (12 + 10x + (6 * x + 5x * x)) = 0 (12 + 10x + (6x + 5x2)) = 0 Combine like terms: 10x + 6x = 16x (12 + 16x + 5x2) = 0 Solving 12 + 16x + 5x2 = 0 Solving for variable 'x'. Factor a trinomial. (2 + x)(6 + 5x) = 0Subproblem 1
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Subproblem 2
Set the factor '(6 + 5x)' equal to zero and attempt to solve: Simplifying 6 + 5x = 0 Solving 6 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = 0 + -6 5x = 0 + -6 Combine like terms: 0 + -6 = -6 5x = -6 Divide each side by '5'. x = -1.2 Simplifying x = -1.2Solution
x = {-2, -1.2}
| -10x+10=-40 | | -5.2(4s+6)-1.7(2s-4)= | | 3(2x+15)=2x+20 | | -5-8x=5 | | 2.8x+1y=747.7 | | 2(x-4)=42 | | -100x-300=300 | | 3z+8=-2z+13 | | c(c-5)=0 | | 27=3/4(y) | | s^3+2s^2-25s=50 | | 6[5-(4x-4)]+7x=0 | | 4w+7=7w-14 | | 3x^2+26x+73=0 | | -5u-8=-2u+1 | | 91=9f+28 | | x+3(x-3)=3x+2+2x | | -3f+-11=70 | | a^2-8=2a | | 9(x-5)-4x=-5 | | 9v-6=9v+-6 | | 6v-27=-3v | | Cos*2*x=cos*x | | 2sin^2(x)-5sin(x)+2=0 | | -2u+2=4 | | 6y+27=9y+18 | | 4+3(10x+7)=-5 | | 5x*9= | | v^4+100=29v^2 | | (-2x^2)*(-x^2)= | | 3(x)-2=-7 | | 2x-5+5=13+5 |